Using Technology to Promote Therapist Use of Exposure Therapy for Childhood Anxiety Disorders: A Randomized Pilot Study. Issue 4 (July 2022) - Whiteside, Stephen P.H.; Biggs, Bridget K.; Ollendick, Thomas H.; Dammann, Julie E.; Tiede, Michael S.; Hofschulte, Deanna R.; Reneson-Feeder, Stephanie; Cunningham, Megan; Sawchuk, Nicholas R.; Geske, Jennifer R.; Brennan, Elle
Highlights: Community therapists do not provide exposure for childhood anxiety disorders (CADs) We examined brief training in technology-assisted exposure therapy for CADs. Community therapists increased their openness to, and use of, exposure. Exposures were more often imaginal and of limited intensity compared to benchmarks. Patient outcomes were not improved, perhaps due to lower quality of exposure. Abstract: Increasing the use of exposure by community therapists during the treatment of childhood anxiety disorders is critical to improving the quality of available treatment. The aim of the current study was to investigate whether a brief training in the delivery of an exposure-focused and technology-assisted treatment protocol increased community therapist openness to exposure therapy, use of exposure in treatment, and improvement in patient symptoms. Participants were 17 therapists recruited from a large health system to provide outpatient therapy to 32 youth ages 8–18 ( M = 12.13, 78.1% girls) with treatment as usual or with the Anxiety Coach application (AC-app). Consistent with two of three hypotheses, therapists in the AC-app condition increased their openness to, and use of, exposure—however, these changes did not translate into improved therapeutic outcomes. Comparisons to benchmark studies suggest that the community therapists did not implement enough in vivo exposure of sufficient intensity or include parents enough to improve outcome. Results support the ability of exposure-focused treatment protocols to increase community therapists' use of evidence-based treatment and suggest that future efforts should focus on improving the quality, in addition to quantity, of therapist-delivered exposure.